Changes in taxonomic and functional diversity of an urban stream fish assemblage: A 30-year perspective - Antoniazzi, Reuber; Montaña, Carmen G.; Peterson, David; Schalk, Christopher M. (Frontiers in Environmental Science, 2023)
Globally, freshwater fish diversity is declining, and decreasing at a faster rate in response to urbanization. Time series of freshwater fish communities can help elucidate the underlying mechanisms of species loss and change, as well as inform conservation strategies. Traditional approaches to understand the dynamics of fish assemblage focused on taxonomic diversity. However, using complementary analytical methods, such as functional diversity can help develop a stronger predictive framework on the effects of the species loss or persistence in streams that are increasingly urbanized. We assessed temporal changes of fish assemblages in an urban stream in East Texas between 1989-1990 and repeated between 2018-2019. We explored the similarities and differences in species richness, composition, and functional diversity of fishes. Although the species richness and functional richness between the two time periods were similar, we observed changes in species composition. In addition, higher functional dispersion and evenness were observed for the contemporary assemblage compared with the historical assemblage. Some fish species were locally extirpated, while others colonized the system, increasing the functional diversity of the current assemblage. Urbanization has commonly been associated with declines in diversity and richness, however, our findings suggest that it also plays a role in adding few invasive generalist species and native tolerant of human disturbance. East Texas streams support very diverse fish assemblages, with some sentinel species (e.g., imperiled shiners) rapidly responding to stream alterations. Multiple stressors can underlie the dynamics and composition of fish assemblages; thus, it is essential for more comparative studies of current and historical data of fish assemblages. Likewise, studies targeting sentinel fish species may have more utility for the evaluation of freshwater ecosystems.